Performance Evaluation of Concrete Incorporating Roof Tile Waste as Coarse Aggregate Replacement and Fosroc Conplast WP421 Admixture - Agyanata Tua Munthe; Romadhon; Syafwandi (Momentum International Journal of Civil Engineering (MIJCE), 2026)
The increasing demand for concrete in construction has encouraged the exploration of sustainable materials to reduce the consumption of natural resources and utilize construction waste. Roof tile waste has potential as a partial substitute for coarse aggregate, while chemical admixtures such as Fosroc Conplast WP421 can improve concrete workability and performance. This study aimed to evaluate the effects of roof tile waste and Fosroc Conplast WP421 on the workability and compressive strength of concrete. An experimental laboratory method was employed using cylindrical concrete specimens with a diameter of 150 mm and a height of 300 mm. Fosroc Conplast WP421 was added at 1.3% of cement weight, while roof tile waste was used as a 30% replacement for coarse aggregate. Slump tests and compressive strength tests were conducted at curing ages of 7, 14, and 28 days. The results indicated that the addition of Fosroc Conplast WP421 increased the slump value from 13.5 cm in normal concrete to 18.0 cm in concrete containing 30% roof tile waste. The highest compressive strength at 28 days was obtained by concrete containing 1.3% Fosroc Conplast WP421 without roof tile waste, reaching 39.65 MPa, while the mixture with 30% roof tile waste achieved 37.73 MPa. It can be concluded that Fosroc Conplast WP421 improved concrete workability and maintained satisfactory compressive strength. Further studies are recommended to investigate different replacement ratios and long-term durability performance. The findings contribute to the development of more sustainable concrete materials through waste utilization.